(untitled) (The International Conference on Sustainable Economics Management and Accounting Proceeding, 2026)
Underpricing remains a significant issue in the Indonesian IPO market, with inconsistent findings regarding the influence of underwriter reputation and firm size. This study aims to examine the effect of underwriter reputation and firm size on IPO underpricing on the Indonesia Stock Exchange during the 2023–2024 period. The study employs signaling theory as a conceptual framework, where both variables act as quality signals for investors to reduce information asymmetry. Using multiple linear regression with classical assumption tests, this study analyzes companies conducting IPOs within the observation period. The results show that underwriter reputation has a negative but statistically insignificant effect on underpricing, indicating that it is not a dominant factor influencing investor decisions. In contrast, firm size has a negative and significant effect, suggesting that larger companies tend to experience lower levels of underpricing. These findings support signaling theory, where firm size serves as a credible indicator of company quality. This study contributes to enhancing transparency and accountability in financial reporting, which are essential elements of sustainability-oriented accounting. Furthermore, transparent financial information in IPO processes supports sustainable investment decisions and strengthens the credibility of capital markets.